2011
DOI: 10.3324/haematol.2010.039099
|View full text |Cite
|
Sign up to set email alerts
|

Successful generation of primary virus-specific and anti-tumor T-cell responses from the naive donor T-cell repertoire is determined by the balance between antigen-specific precursor T cells and regulatory T cells

Abstract: The online version of this article has a Supplementary Appendix. BackgroundOne of the major challenges in allogeneic stem cell transplantation is to find a balance between the harmful induction of graft-versus-host disease and the beneficial graft-versus-leukemia and pathogen-specific immune responses. Adoptive transfer of in-vitro generated donor T cells with specific anti-leukemic or pathogen-specific activity may be effective. However, in many cases this requires the in-vitro priming and expansion of antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…19 Although these data are of relatively low significance because of the small sample size, they are consistent with previous results of several investigators including ourselves showing that naive-depleted (or memory-enriched) CD8 þ T cells contained very low numbers of leukemia-reactive T cells, 6,[20][21][22][23] regardless which T-cell differentiation marker including CD45RA was used for cell selection. This suggests the use of CD45RA-depleted DLIs preferentially in situations where the risk of leukemia relapse is low or the disease is nonmalignant.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…19 Although these data are of relatively low significance because of the small sample size, they are consistent with previous results of several investigators including ourselves showing that naive-depleted (or memory-enriched) CD8 þ T cells contained very low numbers of leukemia-reactive T cells, 6,[20][21][22][23] regardless which T-cell differentiation marker including CD45RA was used for cell selection. This suggests the use of CD45RA-depleted DLIs preferentially in situations where the risk of leukemia relapse is low or the disease is nonmalignant.…”
Section: Discussionsupporting
confidence: 79%
“…25 Also replenishment of DLIs with in vitro produced leukemia-reactive T cells from the CD45RA þ naive-enriched T-cell subset may be an option. [21][22][23] In conclusion, clinical grade depletion of naive T cells from entire LPs is feasible and highly efficient using magnetic CD45RA beads and the CliniMACS device. The CD45RA À target fraction contains effector and central memory T cells that show preserved reactivity to common viral and fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…To allow efficient in vitro priming of naive antigen-specific precursor T cells, Treg-cell depletion of the responder T-cell populations has been applied [21]. However, this Treg-cell depletion in combination with priming with autoDCs as professional APCs may allow the outgrowth of autoreactive T cells that are under normal circumstances kept silent by Treg cells [20,[22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these strategies are only applicable when the donor has immunity to the viruses. More recent attempts to overcome this limitation via manipulation of culture conditions to allow expansion of virus-specific cells in primary immune responses ex vivo are showing some promise (Park et al, 2006;Jedema et al, 2011), though clinical application has yet to be reported. Given that such cells, particularly the CD8 compartment, have been reported to recognize unconventional CMV epitopes (Hanley et al, 2009), the results of clinical application are keenly awaited.…”
Section: Cellular Immunotherapymentioning
confidence: 99%